Effects of citizen participation on urban water management based on socioeconomic factors - F. Mardianti; D.E. Purba (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: In this era of globalization, clean water management is considered a complex problem requiring the strategic management of various aspects. Citizen participation in managing polluted waters is a critical, determining factor in preventing water crises. This study predicts the socioeconomic factors influencing citizens’ behaviors in polluted water management.METHOD: A survey on Jakarta’s clean water was conducted with 503 respondents in 2022. Three interest variables were studied: first action taken during contamination, water nuisance level, and willingness to pay for clean water. Control variables were also explored, including daily income, education level, age, marital status, and gender. Data were analyzed using logistic regression.FINDINGS: In general, socioeconomic factors influence citizens’ behaviors in dealing with polluted water. The specific findings regarding the probabilities for the first action on the basis of asking for immediate action from local authorities, namely, by asking other citizens, waiting for information from other citizens, and looking for sources of water pollution were –2.21, –3.50, and 0.61, respectively. The results also revealed the probabilities of nuisance level (0.07), willingness to pay for clean water (0.0495), daily income (–0.02), educational level (–0.429), and age (0.01). The probabilities for married citizens (–2.845) and men (–0.268) were lower than those for unmarried citizens and women, respectively.CONCLUSION: The findings of this study can be used to predict the management of water pollution among Jakarta citizens, as well as serve as a reference for related stakeholders. Socioeconomic factors can affect citizens in various aspects of life, including participation in water management. However, not all socioeconomic factors are directly proportional to citizen participation. In fact, other socioeconomic indicators are inversely proportional to what are expected based on theoretical assumption. Finally, educational level and income do not always translate to behavioral changes linked to water pollution management.